Impact of electric vehicles on power quality in a smart grid context - Monteiro, Vítor Duarte Fernandes (2011)
The large dependency of the imported fossil fuels and the soaring oil prices, makes essential the look for alternatives to the traditional people transportation system. The natural bet is the electric mobility, namely Electric Vehicles (EV), and Plug-in Hybrid Electric Vehicles (PHEV). This way, in this paper is analyzed the potential impacts of the battery charging systems on the grid power quality, in a Smart Grid context. It is considered the current consumed, according to a typical electric consumption profile, and the voltage degradation for a large number of houses. Two different types of EV batteries chargers were considered: a traditional charger; and a smart charger with sinusoidal current consumption and unitary power factor. It presents simulation results of the integration of EVs and PHEVs in terms of power quality, and experimental results of a smart charger which was specially developed for EV charging and that allows mitigation of the power quality degradation.